Demographic and facility volume related outcomes in radiofrequency ablation for early-stage hepatocellular carcinoma. Issue 7 (July 2019) - Lam, Alexander; Yoshida, Emi J.; Bui, Kevin; Katrivesis, James; Fernando, Dayantha; Nelson, Kari; Abi-Jaoudeh, Nadine
Abstract: Background: To evaluate outcomes related to disparities in facility volume and patient demographics in patients with early-stage hepatocellular carcinoma (HCC) treated with radiofrequency ablation (RFA). Methods: This is a retrospective study of patients with stage I/II HCC treated with RFA in the National Cancer Database. Independent contributors to overall survival were determined with Cox regression analysis. The Kaplan–Meier method and log-rank analyses were used to estimate overall survival and compare survival curves. A propensity score matched cohort analysis was performed. P-values < 0.05 were considered statistically significant. Results: In total, 2911 patients were included. Stage II disease (p-value = 0.006), increasing alpha fetoprotein (p-value = 0.007), and increasing bilirubin (p-value < 0.001) were associated with worse survival. Improved survival was seen in patients treated at high-volume centers (p-value = 0.004), which persisted following propensity score adjustment (p-value = 0.003). Asian race was associated with significantly improved survival (p-value < 0.001), while governmental insurance was associated with a significant decrease in survival (p-value < 0.001). Conclusion: Treatment at a high-volume center and Asian race were signiﬁcantly associated with improved survival following RFA for early-stage HCC. Governmental insurance, increasing alpha fetoprotein, increasing bilirubin, and higher disease stage were signiﬁcantly associated with worse survival.